Recognition in the biography of Hussein Barghouthi " Among the Almond Trees" - Benssokhri, ZOUBEYR (Milev Journal of Research and Studies, 2022)
Recognition has constituted an important theme in contemporary philosophical studies, and whose influence extended to literary texts because of the ability of the latter in revealing its manifestations at various levels. Building personalities, collective self, resistance, and conflict at the level of language and space. Hussein Barghouthi’s biography “Among the Almond Trees” was one of the most important texts that presented the memory and family, their relationship to place, how myths tolerate and exchange recognition in spite of their different cultures in the same collective human being, and how icons struggle at the level of language, self, and place, not to mention the daily reality in which the Israeli attends with his language, weapons, icons, and memories; where the Palestinian/Israeli dichotomy creates a real space for dealing with the theme of recognition.